Corporate Governance Effect on Financial Distress - Christian, Natalis; Angelin (Universitas Gorontalo, 2026)
This study investigates the impact of corporate governance on the likelihood of financial distress among firms listed on the Indonesia Stock Exchange (IDX) during 2017–2023, encompassing the pre-COVID-19, COVID-19, and post-COVID-19 periods. Using panel logistic regression. The analysis examines governance variables, alongside financial controls such as leverage and profitability. Financial distress is measured using the Altman Z-score model. The findings show that leverage is the most consistent and significant predictor of financial distress across all periods. CEO turnover and BOD President turnover are negatively associated with financial distress, indicating their corrective governance role. Conversely, longer BOD President tenure increases distress risk, while longer average BOD tenure reduces it. Overall, financial structure plays a dominant role, while governance effects vary by context, offering insights for strengthening corporate resilience in emerging markets.